The historical archaeology laboratory handbook volume 1 : patterns and analysis - Chenoweth, John M.
The first part of Volume I includes a guide to further research, a new Primer on Historic Ceramics, discussions of the life-course of objects as they are used and reused, fragmentation and missing artifacts, and central information on dating. Part two presents methods of analysis unique to historical archaeology, such as Binford’s Pipe Stem Dating or South's Mean Ceramic Dating formulas in their original forms, updates are discussed in chapter one, along with various iterations of pattern analysis.